(3GdaUhds - (3eMeO Hf eMehO Hf MSjf, eLO GdOjf GdoCrSoQhnTfj,J (B632 (3g` s ((3eMeO Hf jhSa GdaNQi s)
(3ChdgG (B:s
(3hHYO abO bGd eMeO Hf eMehO GdGSJQhTfi deG CdajJ faSi Cdag HeWGdYI MdGFd GdeSGFd heTGgOI ObGFb GdOdGFd s
(3BNQgG (B:s
(3Je GdaUhd ef GdESJQhTfi HYhf Gddg hMSf Jhajbg s
(3HChdg agQSJ ddeNWhWs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1266s
(3eUOQ GbJfGA GdCUd (B:s
(3GdecJHI GdCRgQjI (B((3abg Mfai (B859) s
Keywords: (3Gdabg GdMfajs